2019
DOI: 10.1039/c9dt00499h
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, structures and catalytic properties of Evans–Showell-type polyoxometalate-based 3D metal–organic complexes constructed from the semi-rigid bis(pyridylformyl)piperazine ligand and transition metals

Abstract: Two 3D Evans–Showell-type POM-based different transition metals–bis-pyrazine–bis-amide complexes act as heterogeneous catalysts for the oxidation of benzyl alcohol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Inspired by the remarkable performance of the Evans–Showell type POM [Co 2 Mo 10 O 38 H 4 ] 6− in catalyzing oxidation reactions, 41,42 our group has been interested in understanding whether such POM hybrid frameworks can effectively catalyze the oxidation of sulfides as heterogeneous catalysts. In a six-year-old study, Hou used {Co 2 Mo 10 } units to construct several examples of covalently bonded high-dimensional host–guest hybrid compounds with different organic molecules, achieving efficient catalytic conversion of sulfides in about four hours.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the remarkable performance of the Evans–Showell type POM [Co 2 Mo 10 O 38 H 4 ] 6− in catalyzing oxidation reactions, 41,42 our group has been interested in understanding whether such POM hybrid frameworks can effectively catalyze the oxidation of sulfides as heterogeneous catalysts. In a six-year-old study, Hou used {Co 2 Mo 10 } units to construct several examples of covalently bonded high-dimensional host–guest hybrid compounds with different organic molecules, achieving efficient catalytic conversion of sulfides in about four hours.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic complexes (MOCs) consist of periodically connected metal nodes and organic ligands, [18] which have become one of the most popular heterogeneous catalysts, especially in various catalytic oxidation processes, due to their structural diversity, functional adaptability. [19][20][21] Additionally, metal centers in MOCs are generally considered to be catalytic active sites in these oxidation processes to promote the reaction process. [22][23][24] Sometimes, organic ligands also play a certain role in some organic reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, N-donor ligands containing pyridyl, tetrazole, and imidazole groups have become popular candidates in recent years, due to the fact that the multiple N-donors makes it possible for them to play active roles in the construction of versatile structures and stable POM-based frameworks. [26][27][28] Further, the design of amide derivative ligands containing multiple N/O sites enriched the structures and expanded the application of POM-based complexes. For instance, two Evans-type POMbased complexes constructed from two different bis-pyridinebis-amide ligands, synthesized by Li et al showed excellent catalytic oxidation performance.…”
Section: Introductionmentioning
confidence: 99%